PENGARUH BRAND AWARENESS TERHADAP PERCEIVED QUALITY DAN BRAND LOYALTY SEBAGAI DETERMINAN TERHADAP PURCHASE INTENTION (Studi Kasus: Teh Botol Sosro Di Pasar Festival Kuningan, Jakarta) - Ria E Monarch; Zahrida Z Wiryawan (Jurnal Manajemen., 2012)
This research attempted to analyse and explain whether brand awamesswould have signifant impact on product quality, brand loyalty, and also upon buyerpurchasing decision. It also would investigate the effects of quality perception onpurchasing behavior as well as on purchasing decision of the customers itself. The thirdobjective was to study if there were impacts of the intermediary factors on quality andbrand loyalty upon brand awareness and decision making activities. This study usedTeh Botol Sosro as object of analysis with survey method distributing questionnaires to250 respondents of the Teh Botol Sosro consumers at Pasar Festival Kuningan, JakartaJanuary 2012. The sampling method used was judgmental sampling. Multivariatestatistical data analysis was established by way of Structural Equation Model (SEM),using the AMOS 18 software. The research results indicated that, as seen from theanswers of the respondents, brand awareness directly impacted upon quality perception,brand loyalty, as well as upon purchasing decision. Quality perception had directlyaffected purchasing decision too, while brand loyalty did not directly affectedpurchasing decision. Brand awareness affected purchasing decision through qualityperception, while the latter had no effect upon purchasing decision through brandloyalty.